Effect of three food types on the population growth of Brachionus calyciflorus and Brachionus patulus (Rotifera: Brachionidae - Sarma, S.S.S. (2001)
We compared the population growth of B. calyciflorus and B. patulus using the green alga Chlorella vulgaris, baker’s yeast Saccharomyces cerevisiae or their mixture in equal proportions as food. Food was offered once every 24 h in two concentrations (low: 1x106 and high: 3x106 cells ml-1) separately for each species. The experiments were terminated after 15 days. In general, at any food type or concentration, B. patulus reached a higher population density. A diet of Chlorella alone supported a higher population growth of both rotifer species than yeast alone. B. calyciflorus and B. patulus achieved highest population densities (103±8 ind ml-1 and 296±20 ind. ml-1, respectively) on a diet of Chlorella at 3 x 106 cells ml-1. When cultured using the mixture of Chlorella and yeast, the maximal population densities of B. calyciflorus were lower than those grown on Chlorella. Under similar conditions, the maximal abundance values of B. patulus were comparable in both food types. Regardless of food type and density the rate of population increase per day (r) for B. calyciflorus varied from 0.13±0.03 to 0.63±0.04. These values for B. patulus ranged from 0.19±0.01 to 0.37±0.01. The results indicated that even though Chlorella was a superior food for the tested rotifers, yeast can be effectively used at low concentrations to supplement algal requirements in rotifer culture systems.